Managing Protectionism: The Dairy Industry as a Source of Conflict between Québec and the United States - Holland, Kenneth (Journal of Knowledge Management Practice, 2025)
Canada’s supply management system in dairy has long been a source of friction with the United States, particularly involving Québec, which produces nearly half of Canada’s milk. While most sectors were liberalized under the North American Free Trade Agreement (NAFTA) and its successor, the United States– Mexico-Canada Agreement (USMCA), dairy remains protected by quotas, tariffs, and price controls. The exclusion of American producers—especially in key electoral states such as Wisconsin and Michigan—has made Canadian dairy a repeated target of U.S. presidents. This article examines why supply management persists despite its economic costs. It situates dairy protection in Québec’s provincial identity, language politics, and rural traditions, showing how symbolic politics can outweigh efficiency arguments in a post-material society. It also draws upon the political science theory of entrenchment, which highlights how incumbent actors and interest groups in democratic states use institutional, legal, and strategic tools to resist legislative reform and preserve their advantages. Comparisons with New Zealand, Australia, and the European Union highlight that reform is possible, but also politically costly. The article also contrasts Québec’s defense of dairy with its embrace of liberalized trade in aluminum, steel, aircraft, softwood lumber, and critical and strategic minerals, illustrating the province’s dual international strategies. Finally, it assesses the stakes for the 2026 USMCA review, where U.S. negotiators are likely to press for expanded access to the Canadian dairy market while Québec pushes Ottawa to resist.
Keywords: knowledge management; Canada–United States trade; Québec; dairy sector; supply management; USMCA